Response of Sulphur, Zn and FYM Application on Growth, Yield and Nutrient uptake of Mustard (Brassica juncea (L.) Czern and Coss.) - Patel, Sandeep; Sharma, P. K.; Shahi, S. K.; Tripathi, S. K.; Arvind; Shukla, A. K. (International Journal of Economic Plants, 2023)
The experiment was conducted at the research farm of Department of Agricultural Chemistry and Soil Science, Udai Pratap College (Automous), Varanasi (Uttar Pradesh), during rabi season of 2018–2019 in RBD and replicated thrice. The sowing was done on 29th November 2018. The treatments comprised of three Sulphur levels (20, 40 and 60 kg S ha-1), two Zinc levels (2.5 and 5 kg Zn ha-1) under two levels of FYM (0 and 10 t ha-1) with RDF and control. The mustard variety Varuna was used as a test crop. Application of maximum doses of 60 kg S ha-1+5 kg Zn ha-1+10 t FYM ha-1+RDF produced maximum plant height (170.31 cm), number of branches plant-1 (8.08), number of siliqua plant-1 (117.75), grain yield (855 kg ha-1), straw yield (2480 kg ha-1). whereas control was minimum pronounced, plant height (145.38 cm), number of branch plant-1 (5.25), number of siliqua plant-1 (66.33), grain yield (580 kg ha-1) and straw yield (878 kg ha-1). However, growth parameters, grain yield, stover yield and 1000 grain weight (g) and nutrient uptake increased significantly with increasing dose of Sulphur up to 40 kg and Zn up to 5 kg ha-1.